The Effect of Creative Application Media on Mathematical Representation Ability of Grade IV Elementary School Students - Qurratu'ain, Naurah; Kowiyah , Kowiyah (FKIP - Universitas Riau, 2025)
This research was motivated by students’ difficulties in describing and visualizing mathematical concepts, particularly in plane figure material. Students also struggled to relate these concepts to real-life situations, limiting their ability to apply mathematics in everyday contexts. The research aimed to examine whether the use of the Qreatif Application Media could enhance students’ mathematical representation abilities. A quantitative approach was used with a quasi-experimental design, specifically a nonequivalent group posttest-only control design. Data were collected through tests administered to both the experimental and control classes. Data analysis involved an independent sample t-test and an effect size test. The results showed that the experimental class achieved an average score of 89.61 in mathematical representation ability, while the control class averaged 77.19. The t-test yielded a significance value of 0.000 < 0.05, indicating a significant difference between the two groups. Therefore, it can be concluded that the use of the Qreatif Application Media had a positive impact on students’ mathematical representation abilities in plane figure material compared to conventional teaching methods.